Modeling and Control of Torsional Vibration in Rotating System Using Dual Loop Controllers - Matrood, Mustafa Mohammed; Nassar, Ameen Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2021)
A torsional rotating system is considered for the investigation of passive vibration control using dual loop controllers Proportional-Integral-Derivative (PID) with derivative (D) gain and Proportional – Derivative (PD) with Integral (I) controllers. The controllers are used as low pass filters. Simulation of the models using Matlab-Simulink have been built in this work for torsional vibration control. A comparison between the two controllers with uncontrolled system have been carried out. Results show that the PD – I control is the best method which gives better stability response than the PID – D control.